Dynamic Behavior of a 10 MW Floating Wind Turbine Concrete Platform under Harsh Conditions - Chen, Xiaocui; Wang, Qirui; Zhang, Yuquan; Zheng, Yuan (Mathematics (Basel), 2024)
To ensure the safe and stable operation of a 10 MW floating wind turbine concrete platform under harsh sea conditions, the fluid–structure coupling theory was used to apply wind, wave, and current loads to a concrete semi-submersible floating platform, and strength analysis was performed to calculate its stress and deformation under environmental loads. Moreover, the safety factor and fatigue life prediction of the platform were also conducted. The results indicated that the incident angles of the environmental loads had a significant impact on motion response in the surge, sway, pitch, and yaw directions. As the incident angles increased, the motion response in the surge and pitch directions gradually decreased, the motion response in the sway direction gradually increased, and the yaw motion response showed a trend of first increasing and then decreasing. In addition, the maximum stress of the floating platform under harsh sea conditions was 12.718 MPa, mainly concentrated at the connection of the middle column and pontoon and the connection of the heave plate and Y-shaped pontoon, which meets the use strength requirements. However, the stress concentration zone exhibited a significantly shorter fatigue life with a magnitude of 106. This implies a higher susceptibility to fatigue damage and the potential occurrence of structural failure. This research holds paramount significance in ensuring the safe and stable operation of floating wind turbine platforms, particularly under harsh sea conditions.